KOMUNIKASI PERSUASIF DALAM PEMBENTUKAN SIKAP MENTAL DAN KARAKTER - Astri Widya Maya (Jurnal Prodi Ilmu Komunikasi, 2023)
Persuasive is a complex communication process carried out by an individual or group to obtain (intentionally or unintentionally) a certain response from other individuals or groups verbally and non-verbally and in a subtle and humane manner so that the communicant is willing to do something with pleasure. . The purpose of this study was to find out Persuasive Communication in the Formation of Mental Attitudes and Character (Study on Education Trainers for Indonesian Armed Forces AD KODAM II SWJ Palembang). The research method used is a qualitative method using a case study approach. The results of the study show that trainers (persuaders) use persuasive communication to students (persuadee) in military education with a personal approach when counseling/counseling parents, as well as directions through examples from trainers. At these moments, coaches tend to position themselves as older brothers, fathers, siblings or friends of students. Persuasive communication will be more effective, because it can go both ways. Then according to prospective enlisted members (catam) that this enlisted education is really useful in shaping the character and mentality of the members especially by instilling the character and attitude given by the coaches. Keywords: Persuasive, attitude, Character.